2005
DOI: 10.1007/s00425-005-1546-0
|View full text |Cite
|
Sign up to set email alerts
|

Characterization and dynamic analysis of Arabidopsis condensin subunits, AtCAP-H and AtCAP-H2

Abstract: Condensin complexes are thought to play essential roles in mitotic chromosome assembly and segregation in eukaryotes. To date, two condensin complexes (condensin I and II) have been identified. Both complexes contain two structural maintenance of chromosome (SMC) subunits and three non-SMC subunits. In plants, little is known about the localization and function of all the condensin subunits. Here, we report the analyses on the localization of a non-SMC subunit of Arabidopsis condensin I and II, AtCAP-H, and At… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
32
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
8
2

Relationship

3
7

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 37 publications
5
32
0
Order By: Relevance
“…A 3.9-kb RCD1 genomic sequence, which covered entire RCD1 coding region, was amplified by PCR using a pair of primers, 5 0 -CACCACCCAATAAGATTTCGACGTT-3 0 and 5 0 -AGGAGAACCACAAAGGCAGGTAG-3 0 , and cloned in a Gateway entry vector pENTR/D-TOPO (Invitrogen, Carlsbad, CA, USA). The genomic fragment was then inserted into pGWB8 binary vector downstream of the 35S promoter of cauliflower mosaic virus 10) by the Gateway system (Invitrogen) and introduced into Agrobacterium tumefaciens strain pGV2260. The nucleotide sequence was confirmed by sequencing.…”
Section: )mentioning
confidence: 99%
“…A 3.9-kb RCD1 genomic sequence, which covered entire RCD1 coding region, was amplified by PCR using a pair of primers, 5 0 -CACCACCCAATAAGATTTCGACGTT-3 0 and 5 0 -AGGAGAACCACAAAGGCAGGTAG-3 0 , and cloned in a Gateway entry vector pENTR/D-TOPO (Invitrogen, Carlsbad, CA, USA). The genomic fragment was then inserted into pGWB8 binary vector downstream of the 35S promoter of cauliflower mosaic virus 10) by the Gateway system (Invitrogen) and introduced into Agrobacterium tumefaciens strain pGV2260. The nucleotide sequence was confirmed by sequencing.…”
Section: )mentioning
confidence: 99%
“…In this study, we characterized two of these mutants, heb1-1 and heb2-1, and found that HEB1 and HEB2 encode chromosomal-associated protein (CAP)-G2 and CAP-H2, respectively, two subunits of the chromosomal protein complex known as condensin II (Fujimoto et al, 2005).…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates timely sister chromatid compartmentalization and faithful chromosome segregation during cell division. Eukaryotic condensin complex subunits are conserved from yeast to human (Fujimoto et al, 2005;Hirano, 2005). In budding yeast Saccharomyces cerevisiae, the condensin complex is composed of five polypeptides, including the SMC heterodimer (Smc2p and Smc4p) and three non-SMC subunits (Brn1p, Ycs4p and Ycs5p/Ycg1p) (Freeman et al, 2000).…”
Section: Introductionmentioning
confidence: 99%